Pro-aging effects of glucose signaling through a G protein-coupled glucose receptor in fission yeast. - Antoine E Roux; Alexandre Leroux; Manal A Alaamery; Charles S Hoffman; Pascal Chartrand; Gerardo Ferbeyre; Luis A Rokeach (PLoS Genetics)
Glucose is the preferred carbon and energy source in prokaryotes, unicellular eukaryotes, and metazoans. However, excess of glucose has been associated with several diseases, including diabetes and the less understood process of aging. On the contrary, limiting glucose (i.e., calorie restriction) slows aging and age-related diseases in most species. Understanding the mechanism by which glucose limits life span is therefore important for any attempt to control aging and age-related diseases. Here, we use the yeast Schizosaccharomyces pombe as a model to study the regulation of chronological life span by glucose. Growth of S. pombe at a reduced concentration of glucose increased life span and oxidative stress resistance as reported before for many other organisms. Surprisingly, loss of the Git3 glucose receptor, a G protein-coupled receptor, also increased life span in conditions where glucose consumption was not affected. These results suggest a role for glucose-signaling pathways in life span regulation. In agreement, constitutive activation of the Galpha subunit acting downstream of Git3 accelerated aging in S. pombe and inhibited the effects of calorie restriction. A similar pro-aging effect of glucose was documented in mutants of hexokinase, which cannot metabolize glucose and, therefore, are exposed to constitutive glucose signaling. The pro-aging effect of glucose signaling on life span correlated with an increase in reactive oxygen species and a decrease in oxidative stress resistance and respiration rate. Likewise, the anti-aging effect of both calorie restriction and the Deltagit3 mutation was accompanied by increased respiration and lower reactive oxygen species production. Altogether, our data suggest an important role for glucose signaling through the Git3/PKA pathway to regulate S. pombe life span.